2011
DOI: 10.1002/jcb.23358
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of the cavin family proteins in breast cancer

Abstract: Caveolae are abundant membrane domain on the cell surface of many mammalian cell types and are implicated in a wide range of physiological processes. The caveolae structural protein caveolin-1 is often mutated or deregulated in cancer, and cavin family protein serum deprivation response factor-related gene product that binds to C-kinase (SRBC) has been found to be epigenetically inactivated in lung, breast, and gastric cancer. Both caveolin-1 and SRBC have been proposed to function as tumor suppressors. Polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 23 publications
2
55
1
2
Order By: Relevance
“…The background and mechanisms behind the kiss-and-run phenomenon of caveolae is largely unknown, but it might serve as a surface-buffering system for control of membrane tension, lipid homeostasis or signalling. Cavin3 has, similar to caveolin and caveolae, been heavily implicated in various types of cancer where it appears to act as a tumour suppressor (Bai et al, 2012;Xu et al, 2001). Although the precise role that cavin3 plays to prevent cancer development is not known, the proposed function as a positive regulator of caveolae dynamics might explain its impact on human health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The background and mechanisms behind the kiss-and-run phenomenon of caveolae is largely unknown, but it might serve as a surface-buffering system for control of membrane tension, lipid homeostasis or signalling. Cavin3 has, similar to caveolin and caveolae, been heavily implicated in various types of cancer where it appears to act as a tumour suppressor (Bai et al, 2012;Xu et al, 2001). Although the precise role that cavin3 plays to prevent cancer development is not known, the proposed function as a positive regulator of caveolae dynamics might explain its impact on human health.…”
Section: Discussionmentioning
confidence: 99%
“…The role of cavin3 at caveolae is less clear and cavin3-knockout mice show no apparent defect in caveolae biogenesis (Hansen et al, 2013;Liu et al, 2014). Cavin3 was originally characterised as a protein kinase C substrate, and many studies have highlighted the importance of this protein as a tumour suppressor (Bai et al, 2012;Wikman et al, 2012;Xu et al, 2001). Cavin3 localises to both surface-associated caveolae and internalised caveolae, termed cavicles, and has been proposed to influence trafficking of cavicles inside the cell (McMahon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[130] In breast cancer, the Cavin1 expression is down-regulated as a result of methylation of the Cavin1 promoter. [131] Cavin1 play also a role in the MDR in breast cancer. [132] Indeed, Cavin1 is necessary for MDR in cancer cells via the fortification of lipid rafts.…”
Section: Caveolae New Partners and Cancermentioning
confidence: 99%
“…[137] Cavin3 is also down-regulated in breast cancer cell lines and breast tumor tissue. [131] Cavin3 may repress matrix metalloproteinase-9 transcriptional regulation and act as tumor suppressor in controlling the invasive potential of cells. [138] It was also observed that the DNA methylation of Cavin3 is associated with the acquisition of chemoresistance to the in colorectal cancer.…”
Section: Caveolae New Partners and Cancermentioning
confidence: 99%
“…10 Sonuç olarak caveola potansiyel bir tedavi hedefidir ve Cavin ailesi proteinlerinin ekspresyonu meme kanseri progresyonunun kullanışlı bir prognostik işareti olabilir.…”
Section: şEkil 11 Cavin 1 Geninin 17q212 Kromozomal Lokalizasyonuunclassified